Males and females have different muscle activity patterns during gait after ACL injury and reconstruction - Arhos, E. K.; Di Stasi, S.; Hartigan, E. H.; Snyder-Mackler, L. (Journal of Electromyography and Kinesiology, 2022)
Kinematic and kinetic changes following anterior cruciate ligament (ACL) rupture and reconstruction (ACLR) have been fundamental to the understanding of mechanical disrupted load as it contributes to the development of posttraumatic osteoarthritis. These analyses overlook the potential contribution of muscle activity as it relates to the joint loading environment. Males and females classified as non-copers present with unique knee kinematics and kinetics after ACL injury. The purpose of this study was to perform sex-specific analyses in these individuals to explore muscle activity timing during gait after ACL rupture. Thirty-nine participants (12 females, 27 males) were enrolled. Muscle activity during gait was evaluated before and after pre-operative physical therapy, and six months after ACLR. Surface electromyography data were evaluated to determine timing (e.g., the time the muscle activity begins (`On`) and ends (`Off`)) for seven muscles: vastus lateralis and medialis (VL, VM), lateral and medial hamstrings (LH, MH), lateral and medial gastrocnemius (LG, MG), and soleus (SOL). General linear models with generalized estimating equations detected the effects of limb and time for muscle activity timing. Males presented with more limb asymmetries before and after pre-operative PT in the VL On (p < 0.001) and Off (p = 0.007), VM On and Off (p < 0.001), and MH off (p < 0.001), but all limb differences resolved by six months post ACLR. Changes in muscle activity in males were pervasive over time in both limbs. Females presented with no interlimb differences pre-operatively, and only involved limb VL off (p = 0.027) and VM off (p = 0.003) and the LH off in both limbs (p < 0.038) changed over time. Our data indicate that inter-limb differences in muscle activity across time points and changes in muscle activity timing over the course of physical therapy were sex specific. Males presented with more inter-limb differences in muscle activity across time points, and females presented with fewer asymmetries before and after pre-operative physical therapy. These data support that sex-specific adaptations should be taken into consideration when assessing biomechanical changes after ACLR.